GAMBARAN URINALISA PASIEN HIPERTENSI RAWAT INAP DAN RAWAT JALAN DI RUMAH SAKIT LABUANG BAJI - Tadjuddin Naid; Fitriani Mangarengi; Nursina Nursina (Fakultas Farmasi UMI, 2013)
A research has been done about urinalysis profile on patient hypertension inpatient and outpatient at Labuang Baji Hospital was performed. The aim of this research was to determine urinalysis profile on hypertension patient. This research is an descriptive study with cross sectional method with total amount of sample was 30 samples. The research result showed that hypertension patient who have hypertension grade 1 found on 23 (76.7%) people and there were 7 (23.3%) people who have hypertension grade II with urinalysis profile as the following, the most numerous age groups were 46-50 years old (50.0%), where females (66.7%) most numerous than males (33.3%) and the most numerous hypertension grade I found on inpatient (84.2%) than the outpatient (63.6%) and most numerous hypertension grade II found on inpatient (36.4%) than outpatient (15.8%). Urinalysis profile in hypertension grade I almost same with hypertension grade II but there was difference profile in hypertension grade II such as protein, ascorbic acid increase compared hypertension grade I.Key words: Urinalysis, hypertension, glucose, protein, ascorbic acid